2018
DOI: 10.1534/g3.118.200232
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of Multidrug and Toxic Compound Extrusion (MATE) Family inGossypium raimondiiandGossypium arboreumand Its Expression Analysis Under Salt, Cadmium, and Drought Stress

Abstract: The extrusion of toxins and substances at a cellular level is a vital life process in plants under abiotic stress. The multidrug and toxic compound extrusion (MATE) gene family plays a large role in the exportation of toxins and other substrates. We carried out a genome-wide analysis of MATE gene families in Gossypium raimondii and Gossypium arboreum and assessed their expression levels under salt, cadmium and drought stresses. We identified 70 and 68 MATE genes in G. raimondii and G. arboreum, respectively. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 99 publications
5
37
0
Order By: Relevance
“…Although it is complicated to regulate alkali-salt stress in root, regulation of oxidation-reduction was performed in all stages. The results obtained were in agreement to previous findings in which similar GO terms have been identified for various stress responsive genes such as LEA genes [25], MATE genes [31] among others.…”
Section: Go Enrichment Analysissupporting
confidence: 92%
“…Although it is complicated to regulate alkali-salt stress in root, regulation of oxidation-reduction was performed in all stages. The results obtained were in agreement to previous findings in which similar GO terms have been identified for various stress responsive genes such as LEA genes [25], MATE genes [31] among others.…”
Section: Go Enrichment Analysissupporting
confidence: 92%
“…Previous studies have localized MATE transporters to the plasma membrane, chloroplast, cytoplasm, vacuole, and endoplasmic reticulum, as well as extracellularly [ 24 , 38 , 39 ]. Here, we found the highest proportion localized in the plasma membrane (109 genes), accounting for >80% of all BnaMATE genes in B. napus ; four genes were expressed in chloroplasts and 11 genes were expressed in the vacuoles.…”
Section: Resultsmentioning
confidence: 99%
“…LEA proteins function in a large spectrum of cellular processes, from growth to stress response ( Xiao et al, 2007 ; Campos et al, 2013 ; Pathak and Ikeno, 2017 ). In vascular plants, LEA proteins are highly expressed in embryos during the late embryogenesis stage and in vegetative organs under drought stress conditions, indicating that these proteins play an adaptive role in water limitation ( Dure and Chlan, 1981 ; Baker et al, 1988 ; Lu et al, 2018 ). Previous studies showed that some LEA proteins are involved in ABA signaling and protect cells against stresses, especially osmotic stress ( Hu et al, 2008 ; Candat et al, 2014 ; Lim et al, 2015c ).…”
Section: Introductionmentioning
confidence: 99%